CETM: a conflict-free energy efficient transmission policy in mobile cloud computing. (2018) - Pati, Bibudhendu; Panigrahi, Chhabi Rani; Sarkar, Joy Lal
The rapid advancement of mobile devices creates huge interest to the users for performing various applications. For running those applications, sufficient energy is required which can fulfil the user requirements. To accommodate this challenge, in this work an energy optimal scheduling policy for mobile cloud computing (MCC) named as CETM has been proposed. There are a number of work have been proposed in the literature which focus on energy efficiency of mobile devices but they do not support conflict-free scheduling. In CETM, the applications of mobile devices are split into a number of tasks and the inter release time of two consecutive tasks maintain atleast δ steps. The CETM also supports offloading scheme to reduce the consumption of energy of mobile devices. The simulation results indicate that the proposed approach performs better as compared to the existing approaches such as eTime and ThinkAir .